Mechanosensitive Hydrolysis of ATP and ADP in Lamina Propria of the Murine Bladder by Membrane-Bound and Soluble Nucleotidases - Aresta Branco, Mafalda S. L.; Gutierrez Cruz, Alejandro; Dayton, Jacob; Perrino, Brian A.; Mutafova-Yambolieva, Violeta N. (Frontiers in Physiology, 2022)
Prior studies suggest that urothelium-released adenosine 5’-triphosphate (ATP) has a prominent role in bladder mechanotransduction. Urothelial ATP regulates the micturition cycle through activation of purinergic receptors that are expressed in many cell types in the lamina propria (LP), including afferent neurons, and might also be important for direct mechanosensitive signaling between urothelium and detrusor. The excitatory action of ATP is terminated by enzymatic hydrolysis, which subsequently produces bioactive metabolites. We examined possible mechanosensitive mechanisms of ATP hydrolysis in the LP by determining the degradation of 1,N6-etheno-ATP (eATP) at the anti-luminal side of nondistended (empty) or distended (full) murine (C57BL/6J) detrusor-free bladder model, using HPLC. The hydrolysis of eATP and eADP was greater in contact with LP of distended than of nondistended bladders whereas the hydrolysis of eAMP remained unchanged during filling, suggesting that steps of eATP hydrolysis in the LP appear to be mechanosensitive. eATP and eADP were also catabolized in extraluminal solutions (ELS) that were in contact with the LP of detrusor-free bladders, but removed from the organ chambers prior to addition of substrate. The degradation of both purines was greater in ELS from distended than from nondistended preparations, suggesting the presence of mechanosensitive release of soluble nucleotidases in the LP. The released enzyme activities were affected differently by Ca2+ and Mg2+. The common nucleotidase inhibitors ARL67156, POM-1, PSB06126, and ENPP1 Inhibitor C, but not the alkaline phosphatase inhibitor (-)-p-bromotetramisole oxalate, inhibited the enzymes released during bladder distention. Membrane-bound nucleotidases were identified in tissue homogenates and in concentrated ELS from distended preparations by Wes immunodetection. The relative distribution of nucleotidases was ENTPD1>>ENPP1>ENTPD2=ENTPD3>ENPP1=NT5E>>ENPP8=TNAP in urothelium and ENTPD1>>ENTPD3>>ENPP3> ENPP1=ENTPD2=NT5E>>ENTPD8=TNAP in concentrated ELS, suggesting that regulated ectodomain shedding of membrane-bound nucleotidases possibly occurs in the LP during bladder filling. Mechanosensitive degradation of ATP and ADP by membrane-bound and soluble nucleotidases in the LP diminishes the availability of excitatory purines in the LP at the end of bladder filling. This might be a safeguard mechanism to prevent over-excitability of the bladder. Proper proportions of excitatory and inhibitory purines in the bladder wall are determined by distention-associated purine release and purine metabolism.